2023
DOI: 10.3390/pharmaceutics15030875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Conditions on Forming an Effective G4.0 PAMAM Complex with Doxorubicin

Abstract: In this study, special attention was paid to the correlation between the degree of ionization of the components and the effective formation of the complex under alkaline conditions. Using UV-Vis, 1H NMR, and CD, structural changes of the drug depending on the pH were monitored. In the pH range of 9.0 to 10.0, the G4.0 PAMAM dendrimer can bind 1 to 10 DOX molecules, while the efficiency increases with the concentration of the drug relative to the carrier. The binding efficiency was described by the parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The values of binding constants equal K7.5=2.07×10 6 , K9.0=9.38×10 2 , K9.5=7.01×10 2 and their values decrease with increasing pH. The determined values of binding constants at alkaline conditions are K9.0=9.38×10 2 M -1 and K9.5=7.01×10 2 M -1 and they are close to the values that we obtained in previous work using UV-vis with Hill's method (K9.0=2.39×10 2 and K9.5=2.73×10 2 ) [29]. The value of the binding constant at pH 7.5 is close to that obtained by Chanphai et al for the same system in PBS buffer at physiological pH as well (K=1.6×10 6 ) [44].…”
Section: Binding Constants and Thermodynamic Parameters Of G40-doxsupporting
confidence: 87%
See 3 more Smart Citations
“…The values of binding constants equal K7.5=2.07×10 6 , K9.0=9.38×10 2 , K9.5=7.01×10 2 and their values decrease with increasing pH. The determined values of binding constants at alkaline conditions are K9.0=9.38×10 2 M -1 and K9.5=7.01×10 2 M -1 and they are close to the values that we obtained in previous work using UV-vis with Hill's method (K9.0=2.39×10 2 and K9.5=2.73×10 2 ) [29]. The value of the binding constant at pH 7.5 is close to that obtained by Chanphai et al for the same system in PBS buffer at physiological pH as well (K=1.6×10 6 ) [44].…”
Section: Binding Constants and Thermodynamic Parameters Of G40-doxsupporting
confidence: 87%
“…Since the PAMAM dendrimer efficiently binds doxorubicin under alkaline conditions (pH > 8.5) [29], the stability of the free drug was checked under this environment. UV-vis spectroscopy monitored the spectral changes of doxorubicin in relation to pH (pH=8.5, 9.0, 10.0) at 72h (Figure SM1).…”
Section: Stability and Self-aggregation Of Doxorubicin Under Alkaline...mentioning
confidence: 99%
See 2 more Smart Citations
“…They have shown that at a pH 9.0–10.0, the chemodrug and the dendrimer form stable complexes, where one dendrimer molecule can bond 1 to 10 molecules of doxorubicin. The complexes also possess high fluorescence intensity, which can be useful for theranostics [ 7 ].…”
mentioning
confidence: 99%